2010
DOI: 10.1007/s10528-010-9383-7
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Genetic Variation at the Prolactin-RsaI (PRL-RsaI) Locus in Indian Native Cattle Breeds (Bos indicus)

Abstract: This study assessed the distribution pattern of allelic variants at the prolactin-RsaI locus in 23 Indian native cattle breeds (Bos indicus). PCR-RFLP genotyping of a 156 bp fragment of prolactin (PRL) in exon 3 revealed the predominance of the heterozygous AB genotype (mean frequency 0.58) irrespective of utility type (dairy, dual, draft), geographic region (northern, central, southern), and coat color (red, gray) of the breeds analyzed. The overall frequencies of homozygous AA (0.22) and BB (0.20) genotypes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 17 publications
2
18
1
Order By: Relevance
“…The bovine PRL locus is reported to have two alleles, namely, the A and B alleles 8 . Previous research has shown that in HL cattle raised in Russia, South Korea 15 and Lithuania 21 the frequency of the PRL-A allele is higher than that of the B allele.…”
Section: Prolactin (Prl)mentioning
confidence: 99%
See 4 more Smart Citations
“…The bovine PRL locus is reported to have two alleles, namely, the A and B alleles 8 . Previous research has shown that in HL cattle raised in Russia, South Korea 15 and Lithuania 21 the frequency of the PRL-A allele is higher than that of the B allele.…”
Section: Prolactin (Prl)mentioning
confidence: 99%
“…It has been reported that, in cattle, the bGH gene is correlated with certain yield traits, in particular with milk yield and quality, growth 6 , carcass composition and quality 7 . In this context, it is considered that it could be of use as a candidate gene in animal improvement programmes targeted at increasing milk and meat yields 8 . Previous molecular genetic studies have demonstrated that yield traits such as milk yield and body weight gain are correlated with certain polymorphisms of the bGH gene 6 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations